Convenient synthesis of ketal derivatives from cubebin using amberlite as heterogeneous catalyst - Laurentiz, Rosangela da Silva de [UNESP]; Borges, Alexandre [UNESP]; Andrade e Silva, Marcio Luis; Donate, Paulo Marcos (Springer, 2015)
Eleven ketal derivatives were prepared from the natural product cubebin using Amberlite IR-120AR as heterogeneous catalyst and ROH as the source of the alkyl group.
Keywords: Cubebin; Ketal derivatives; Heterogeneous catalysis; Amberlite